Beauty Premium of Working Women in Urban Indonesia - Octafia, Tri Putri; Setyonaluri, Diahhadi (Makara Human Behavior Studies in Asia, 2022)
Being attractive is believed to give many benefits in life. Economic studies have observed that physical attractiveness is associated with a higher wage. The benefits of being attractive have been perceived from early age, to the labor market, and to the marriage market. Despite all the advantages that beauty brings, efforts are being made to achieve or maintain attractiveness. People spend substantial resources,such as time and money, to enhance appearance. Using Ordinary Least Square (OLS) regression, this study examines the correlation between perceived attractiveness and earnings among urban working women in Indonesia. Findings show that the income of women who perceive themselves as attractive is 19% higher than those who are unattractive after makeup application. Meanwhile, attractiveness without makeup application is found uncorrelated with earnings. Thus, grooming behavior may be a source of the observed wage premium for female workers.